Magnesium-based bone tissue regeneration and repair material coated with Fe3O4-coated GaP coating as well as preparation and application of magnesium-based bone tissue regeneration and repair material
By preparing Fe3O4@GaP coating on the surface of magnesium-based materials, the problem of uncontrollable degradation rate and insufficient anti-tumor effect of magnesium alloy bone defect repair materials is solved, and mechanical stability and bone promotherapy are achieved. It is suitable for bone fixation systems and guided bone regeneration membranes.
Patent Information
- Application Number
- CN202510768609.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-10
- Publication Date
- 2025-08-19
AI Technical Summary
The existing magnesium alloy bone defect repair materials have uncontrollable degradation rate, insufficient anti-tumor effect and poor mechanical stability, making it difficult to meet the needs of inhibiting local recurrence and promoting bone regeneration after bone tumor resection.
The Fe3O4@GaP coating is prepared on the surface of the magnesium-based material, and an iron trioxide-doped gallium phosphide coating is formed through phosphating treatment. Combined with electromagnetic vibration technology, the mechanical stability, controllability of the material, anti-tumor performance, and bone-promoting repair ability of the material is improved.
The mechanical stability and bone-promoting repair ability of magnesium-based bone tissue regeneration and repair materials have been achieved, which significantly inhibits tumor cell proliferation, and is suitable for bone fixation systems and guides bone regeneration membranes.
Smart Images

Figure CN120501936A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomedical metal material preparation, and in particular relates to a magnesium-based bone tissue regeneration and repair material covered with an Fe3O4@GaP coating, and the preparation and application thereof. Background Art
[0002] The prognosis and recovery of patients after bone tumor surgery involve multiple biological and clinical factors. Major challenges include the risk of tumor recurrence, bone defect repair, and functional recovery. Surgical resection is the mainstay of treatment for bone tumors such as osteosarcoma and chondrosarcoma, but local recurrence may occur after surgery, especially when residual tumor cells are present at the surgical margins. To reduce the risk of recurrence, adjuvant therapy is often required, such as radiotherapy, chemotherapy (such as methotrexate and cisplatin), or targeted therapy (such as pamidronate to inhibit osteoclast activity). In addition, bone tumor resection often results in large bone defects, the regeneration and repair of which depend on the choice of implant material: although autologous bone transplantation is the gold standard, donor-site complications limit its application; allogeneic bone or artificial bone (such as hydroxyapatite and β-tricalcium phosphate scaffolds) can provide structural support but lack biological activity.
[0003] In recent years, degradable metals have become a research hotspot for bone defect repair materials due to their excellent biocompatibility, mechanical adaptability and osteogenic activity. Among them, the density and elastic modulus of magnesium alloys are similar to those of human bone tissue, which can effectively reduce the stress shielding effect and avoid bone resorption and osteoporosis caused by the large difference in elastic modulus of traditional metal implants. Its high specific strength characteristics can provide stable mechanical support in the early stage of bone healing, and gradually transfer stress stimulation to new bone tissue during the degradation process, promoting bone healing and shaping. Thanks to the comprehensive advantages of magnesium alloys such as unique mechanical properties, degradability, biocompatibility and osteoinductivity, magnesium alloys are particularly suitable for bone defect repair materials. However, most magnesium alloys lack anti-tumor function and it is difficult to meet the dual needs of inhibiting local recurrence and promoting bone regeneration after bone tumor resection. At the same time, the uncontrollable degradation rate of magnesium alloys during the degradation process may cause damage to normal tissues and premature failure of bone implant devices. In order to enhance its anti-tumor effect, gallium salts (Ga 3+ ) and ferroferric oxide (Fe3O4) are currently commonly used anti-tumor additives. 3+Salt blocks the iron uptake of tumor cells by competitively binding to transferrin receptor (TfR1) and inhibits ribonucleotide reductase (RRM2), thereby blocking DNA synthesis and cell cycle, with the advantages of high selectivity and low drug resistance. In addition to anti-tumor effects through magnetic hyperthermia (alternating magnetic field induces local high temperature), Fe3O4 can also use its chemodynamic therapy (catalyzing hydrogen peroxide to generate hydroxyl radicals ·OH) to kill tumors. In addition, Fe3O4 can also provide MRI imaging capabilities and can monitor the effect of tumor treatment in real time. In order to improve the corrosion resistance and mechanical stability of magnesium alloys, phosphating treatment can form a phosphating coating on the surface of magnesium alloys to effectively isolate the erosion of body fluids, thereby ensuring stable load-bearing function during service. In terms of promoting bone repair, gallium phosphide (GaP), as a functional coating with similar physical and chemical properties to hydroxyapatite (HA) bioceramics, can further enhance the osteoblast proliferation, differentiation and mineralization ability of magnesium alloys, and Ga 3+ Ions can inhibit osteoclast activity and promote the improvement of osteoblast performance.
[0004] Therefore, we attempted to prepare a magnesium-based bone tissue regeneration and repair material with a surface-coated iron oxide-doped gallium phosphide (Fe3O4@GaP) coating by performing phosphating treatment on the surface of the magnesium-based material, giving it the synergistic functions of "mechanical stability-anti-tumor-promoting bone repair". Summary of the Invention
[0005] The purpose of the present invention is to address the above-mentioned technical problems and provide a magnesium-based bone tissue regeneration and repair material coated with Fe3O4@GaP coating, which has good mechanical and corrosion stability, controllable degradation rate, and excellent osteogenesis and anti-tumor properties, especially a magnesium-based bone fixation system and guided bone regeneration membrane.
[0006] In view of this, the present invention provides a magnesium-based bone tissue regeneration and repair material covered with a Fe3O4@GaP coating, which includes: a magnesium-based metal substrate and a Fe3O4@GaP coating covered on the surface of the magnesium-based metal substrate.
[0007] Furthermore, the magnesium-based metal matrix is prepared from pure magnesium or Mg-X alloy, wherein X is selected from one or more of Cu, Zn, Sr, Ca, Ge, Ti, Se, Li, Fe, Sn, Ag, Mn, RE, Ga, Zr, and Al.
[0008] Furthermore, in the Mg-X alloy, the total mass content of element X is 0.5-20%, and the rest is Mg.
[0009] The present invention also provides a method for preparing the magnesium-based bone tissue regeneration and repair material coated with the Fe3O4@GaP coating, comprising the following steps: S1, preparation of magnesium-based metal matrix: magnesium-based metal material is melted at high temperature and then cast into an ingot, the ingot is placed in a high-temperature furnace at 350-450°C for homogenization treatment for 4-10 hours and then water-cooled, and then the ingot is subjected to hot extrusion or hot rolling deformation treatment to prepare a magnesium-based metal matrix with a specific shape, and then the magnesium-based metal matrix is surface activated and cleaned; S2, preparation of Fe3O4@GaP coating: Under the action of electromagnetic vibration, the magnesium-based metal substrate is immersed in a phosphating solution heated to 30~80℃ for phosphating treatment for 10~30 minutes, then taken out and washed and dried to obtain a magnesium-based bone tissue regeneration and repair material covered with Fe3O4@GaP coating.
[0010] Furthermore, in step S2: The frequency of the electromagnetic vibration treatment is 10~300Hz, and / or, The electromagnetic vibration treatment mode is frequency modulation or fixed frequency, and / or, The amplitude of the electromagnetic vibration treatment is 0.01~2mm.
[0011] Furthermore, the phosphating solution contains: 0.01-0.5 mol / L gallium nitrate, 0.02-1 mol / L phosphoric acid, 0.005-0.5 mol / L Fe3O4, wherein the particle size of the Fe3O4 is 50-500 nm, and the pH of the phosphating solution is adjusted to 2.5-4.0 with acid or alkali solution.
[0012] Furthermore, in step S1, The ingot is subjected to hot extrusion deformation to prepare a hot extruded magnesium alloy rod, wherein the hot extrusion extrusion ratio is 1:9-36 and the extrusion temperature is 250-450°C; or, The ingot is hot rolled to produce hot-rolled plates or foils, wherein the rolling temperature of the hot-rolled plates and foils is 250-480°C, the deformation amount of each pass is 2-10%, and preheating for 5-10 minutes is performed before each hot rolling pass.
[0013] Furthermore, in step S1, the process of performing surface activation and cleaning treatment on the magnesium-based metal substrate includes: (I) Use sandpaper to remove surface oxides, (II) Rinse with deionized water and alcohol and let dry.
[0014] Furthermore, in step S1, the process of performing surface activation and cleaning treatment on the magnesium-based metal substrate includes: (I) Use sandpaper to remove surface oxides; (II) Rinse with deionized water and alcohol and then dry; (III) placing the magnesium-based metal substrate in a hydrogen flame for high temperature treatment for 3 to 5 minutes; (IV) placing the magnesium-based metal substrate in a reducing atmosphere at 600-800°C for 30-60 minutes; (V) Rinse again with deionized water and alcohol and allow to dry.
[0015] Application of a magnesium-based bone tissue regeneration and repair material coated with Fe3O4@GaP coating in the preparation of a bone fixation system or a guided bone regeneration membrane.
[0016] The beneficial effects of the present invention are: The present invention prepares a magnesium-based bone tissue regeneration and repair material with a surface-coated ferroferric oxide-doped gallium phosphide (Fe3O4@GaP) coating by phosphating the surface of a magnesium-based material. This material has excellent mechanical stability and bone repair-promoting ability, and can significantly inhibit tumor cell proliferation. It can be used to prepare a bone fixation system or a guided bone regeneration membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The surface SEM image and corresponding EDS point scanning results of the Fe3O4@GaP coated WE43 alloy bone plate prepared in Example 1 of the present invention; Figure 2 Polarization curves of the WE43 alloy bone plate with and without Fe3O4@GaP coating in Hanks' solution in Example 1 of the present invention; Figure 3 Statistical graph of the clone morphology and corresponding clone number of DLM8C3H mouse osteosarcoma cells in the extract of WE43 alloy bone plates with and without Fe3O4@GaP coating in Example 1 of the present invention. DETAILED DESCRIPTION
[0018] The following will be combined with the accompanying drawings in the embodiments of the present application to clearly describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field are within the scope of protection of this application.
[0019] In the description of this application, it should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to this application. For ease of description, the dimensions of the various parts shown in the accompanying drawings are not drawn according to the actual proportional relationship. Technologies, methods and equipment known to ordinary technicians in the relevant fields may not be discussed in detail, but where appropriate, the technologies, methods and equipment should be considered as part of the authorization specification. In all examples shown and discussed here, any specific values should be interpreted as merely exemplary and not as limiting. Therefore, other examples of the exemplary embodiments may have different values.
[0020] It should be noted that, in the present application, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device comprising a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the statement "comprises a ..." does not exclude the presence of other identical elements in the process, method, article or device comprising the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in the opposite order according to the functions involved. For example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.
[0021] A magnesium-based bone tissue regeneration and repair material covered with a Fe3O4@GaP coating comprises a magnesium-based metal substrate and a Fe3O4@GaP coating covered on the surface of the magnesium-based metal substrate.
[0022] Furthermore, the magnesium-based metal matrix is prepared using pure magnesium or Mg-X alloy, wherein X is selected from elements non-toxic to the human body, such as one or more of Cu, Zn, Sr, Ca, Ge, Ti, Se, Li, Fe, Sn, Ag, Mn, RE, Ga, Zr, Al, etc.
[0023] Furthermore, in the Mg-X alloy, the total mass content of element X is 0.5-20%, and the rest is Mg.
[0024] The present invention also provides a method for preparing the magnesium-based bone tissue regeneration and repair material coated with the Fe3O4@GaP coating, comprising the following steps: S1, preparation of magnesium-based metal matrix: magnesium-based metal material is melted at high temperature and then cast into an ingot, the ingot is placed in a high-temperature furnace at 350-450°C for homogenization treatment for 4-10 hours and then water-cooled, and then the ingot is subjected to hot extrusion or hot rolling deformation treatment to prepare a magnesium-based metal matrix with a specific shape, and then the magnesium-based metal matrix is surface activated and cleaned; S2, preparation of Fe3O4@GaP coating: Under the action of electromagnetic vibration, the magnesium-based metal substrate is immersed in a phosphating solution heated to 30~80℃ for phosphating treatment for 10~30 minutes, then taken out and washed and dried to obtain a magnesium-based bone tissue regeneration and repair material covered with Fe3O4@GaP coating.
[0025] Furthermore, in step S2: The frequency of the electromagnetic vibration treatment is 10~300Hz, and / or, The electromagnetic vibration treatment mode is frequency modulation or fixed frequency, and / or, The amplitude of the electromagnetic vibration treatment is 0.01~2mm.
[0026] As some examples of the present invention, the parameters of the electromagnetic vibration treatment are a fixed frequency of 100 Hz and an amplitude of 1 mm.
[0027] Furthermore, the phosphating solution contains: 0.01-0.5 mol / L gallium nitrate, 0.02-1 mol / L phosphoric acid, 0.005-0.5 mol / L Fe3O4, wherein the particle size of the Fe3O4 is 50-500 nm, and the pH of the phosphating solution is adjusted to 2.5-4.0 with acid or alkali solution.
[0028] Furthermore, in step S1, The ingot is subjected to hot extrusion deformation to prepare a hot extruded magnesium alloy rod, wherein the hot extrusion extrusion ratio is 1:9-36 and the extrusion temperature is 250-450°C; or, The ingot is hot rolled to produce hot-rolled plates or foils, wherein the rolling temperature of the hot-rolled plates and foils is 250-480°C, the deformation amount of each pass is 2-10%, and preheating for 5-10 minutes is performed before each hot rolling pass.
[0029] Furthermore, in step S1, the process of performing surface activation and cleaning treatment on the magnesium-based metal substrate includes: (I) Use sandpaper to remove surface oxides, (II) Rinse with deionized water and alcohol and let dry.
[0030] Furthermore, in step S1, the process of performing surface activation and cleaning treatment on the magnesium-based metal substrate includes: (I) Use sandpaper to remove surface oxides; (II) Rinse with deionized water and alcohol and then dry; (III) placing the magnesium-based metal substrate in a hydrogen flame for high temperature treatment for 3 to 5 minutes; (IV) placing the magnesium-based metal substrate in a reducing atmosphere at 600-800°C for 30-60 minutes; (V) Rinse again with deionized water and alcohol and allow to dry.
[0031] As some examples of the present invention, the magnesium-based metal matrix is prepared by the following process: First, high-purity metal Mg and Mg-X master alloy are used as raw materials, and the mass ratio of the elements in the pure magnesium or Mg-X alloy components is weighed under the premise of considering the burn-out rate; The raw materials are then placed in a vacuum melting furnace and heated to 650-800°C for melting and then cast into ingots; the ingots are then placed in a muffle furnace heated to 350-450°C for homogenization treatment for 4-10 hours and then water-cooled; the ingots are then hot-extruded and hot-rolled to produce hot-extruded magnesium alloy bars and hot-rolled plates / foils, wherein the extrusion ratio of the hot extrusion is 1:9-36 and the extrusion temperature is 250-450°C; the rolling temperature of the hot-rolled plates and foils is 250-480°C, the reduction is 70-95%, the deformation per pass is 2-10%, and preheating is performed at 250-350°C for 5-10 minutes before each hot rolling pass, ultimately obtaining plates with a thickness of 0.5-3 mm or foils with a thickness of 0.1-0.5 mm; Then use sandpaper to remove the surface oxide, rinse with deionized water and alcohol, and let dry.
[0032] As some examples of the present invention, in step S1, the specific process of performing surface activation and cleaning treatment on the magnesium-based metal substrate is as follows: First, the surface oxide of the magnesium-based metal substrate is removed by sandpaper polishing, and then rinsed with deionized water and alcohol and dried. Then, the magnesium-based metal substrate is placed in a hydrogen flame for high-temperature treatment for 5 minutes. During the high-temperature treatment, the magnesium-based metal substrate is fixed 3 to 8 cm above the burner flame nozzle, and the flame ejected from the burner flame nozzle is used to burn the surface of the magnesium-based metal substrate. If the surface area of the magnesium-based metal substrate is large, the burner flame nozzle or the magnesium-based metal substrate material can be moved so that the surface of the magnesium-based metal substrate can be evenly burned by the flame. At this time, the cumulative time for the flame to burn at all parts of the magnesium-based metal substrate surface should be 3 to 5 minutes. After high-temperature treatment, the magnesium-based metal substrate is placed in a 700°C H2 atmosphere for reduction treatment for 40 minutes; then it is rinsed with deionized water and alcohol again and dried.
[0033] During the aforementioned high-temperature treatment of the magnesium-based metal substrate in a hydrogen flame, hydrogen acts as a fuel and burns in air, with the chemical reaction equation being 2H2 + O2 = 2H2O. However, in actual combustion, due to combustion conditions such as the hydrogen-air mixture ratio and the combustion space structure, it is difficult for hydrogen combustion to achieve a completely ideal state. In addition to the generated water vapor, unreacted hydrogen also remains in the flame, and oxygen from the air also remains in the flame. Furthermore, in complex high-temperature combustion environments, hydrogen may react with trace nitrogen oxides or other impurities in the air to produce reducing gas molecules such as carbon monoxide (CO). Therefore, the flame contains reducing gas molecules such as hydrogen and carbon monoxide, as well as oxygen.
[0034] Because the hydrogen combustion flame is extremely hot, typically reaching thousands of degrees Celsius, this high-temperature environment provides the necessary energy conditions for surface treatment of magnesium alloys, allowing them to reach an active state capable of undergoing physical and chemical reactions. Furthermore, as the flame propagates, the high-speed movement and collisions of gas molecules produce a "shock wave" effect. This "shock wave" propels the gas molecules in the flame to diffuse at high speeds, forming a gas stream with strong momentum. Therefore, when the flame contacts the magnesium alloy, the gas stream quickly impacts the surface, allowing the gas molecules to fully contact the solid surface of the magnesium alloy, triggering a transient, high-temperature, and intense interaction between the gas and solid.
[0035] When a magnesium alloy is burned in a hydrogen flame, its surface is instantly exposed to a mixture of carbon monoxide, hydrogen, and oxygen. The high temperature generated by the flame provides the energy foundation for the interaction between the gas mixture and the magnesium alloy. The moment the flame contacts the magnesium alloy, it acts as a highly efficient energy and material transporter, delivering the gas mixture and high temperature directly to the contact zone between the flame and the magnesium alloy. Within this contact zone, intense diffusion occurs between the gas molecules and the magnesium atoms. Thermal motion continuously diffuses the gas molecules into the magnesium alloy, while the magnesium atoms, energized by the energy, become more active and migrate to the surface. Simultaneously, the presence of oxidizing gases (such as oxygen) and reducing gases (such as carbon monoxide and hydrogen) enables oxidation-reduction reactions to occur, forming a distinct reaction zone on the metal surface.
[0036] In magnesium alloys, reducing gas molecules (such as hydrogen and carbon monoxide) penetrate the alloy's crystal lattice within the reaction zone. At high temperatures, hydrogen can react with certain components within the alloy, such as trace amounts of magnesium oxide or magnesium compounds with other elements. For example, hydrogen reacts with magnesium oxide: MgO + H2 = Mg + H2O. Carbon monoxide may also participate in a similar reaction, generating larger gas molecules such as carbon dioxide (CO2) and water (H2O). As these generated gas molecules accumulate and expand within the magnesium alloy, when their volume exceeds their critical solubility within the alloy, they expand and overflow into the surface area. This expansion and overflow process destroys and reshapes the magnesium alloy's microstructure, forming nanoscale pores on the surface. Furthermore, water vapor can react with magnesium at high temperatures: Mg + H2O = MgO + H2↑, further promoting gas generation and pore formation.
[0037] In a hydrogen combustion flame, magnesium alloys are simultaneously subjected to the combined effects of oxidizing gases (oxygen) and reducing gases (hydrogen and carbon monoxide). Under high temperatures, an oxidation reaction occurs in the magnesium alloy, in which magnesium atoms lose electrons and are oxidized to magnesium ions. These ions then combine with oxygen to form magnesium oxide (MgO), according to the chemical formula 2Mg + O₂ = 2MgO. Simultaneously, the reducing gases (hydrogen and carbon monoxide) may reduce the magnesium oxide to magnesium, for example, MgO + H₂ = Mg + H₂O or MgO + CO = Mg + CO₂. This alternating oxidation-reduction process causes the surface area of the magnesium alloy to cyclically expand and contract. During this volume change, magnesium atoms rearrange themselves, spontaneously diffusing and concentrating on the surface and near the surface. This diffusion and concentration of atoms creates localized nanoscale pores. This redox reaction occurring on the surface of the magnesium alloy can improve the surface state of the magnesium alloy and enhance its corrosion resistance. At the same time, the nanoscale pores formed on the surface of the magnesium alloy can improve the surface state of the magnesium alloy and increase its roughness, making the Fe3O4@GaP coating easy to adhere and able to more stably combine with the surface of the magnesium-based metal matrix and not easy to fall off, further improving the corrosion resistance, bone promotion and anti-tumor properties of the magnesium-based bone tissue regeneration and repair material.
[0038] After the high-temperature flame treatment, the magnesium-based metal substrate is placed in a reducing atmosphere at 600-800° C. for 30-60 minutes to remove oxides on the surface of the magnesium-based metal substrate.
[0039] Application of a magnesium-based bone tissue regeneration and repair material coated with Fe3O4@GaP coating in the preparation of a bone fixation system or a guided bone regeneration membrane.
[0040] As some examples of the present invention, when used to prepare a bone fixation system or a guided bone regeneration membrane, the shape of the magnesium-based bone tissue regeneration and repair material covered with the Fe3O4@GaP coating can be set and processed as needed, for example, the magnesium-based bone tissue regeneration and repair material can be processed into plates, rods, screws, and foils, etc.
[0041] Currently, there are no reports in domestic and foreign literature on a magnesium-based bone tissue regeneration and repair material coated with Fe3O4@GaP with osteogenesis and anti-tumor properties, especially on the preparation method and corresponding performance research of a magnesium-based bone fixation system or guided bone regeneration membrane coated with Fe3O4@GaP. Therefore, the present invention also proposes to use the biodegradable magnesium alloy plate, screw and foil in the next stage of fracture fixation and guided bone regeneration surgery.
[0042] The present invention successfully prepares a degradable magnesium-based bone tissue regeneration and repair material coated with Fe3O4@GaP coating by phosphating pure magnesium and / or Mg-X alloy plates, screws and foils under electromagnetic vibration, which has good mechanical-corrosion stability, controllable degradation rate, excellent osteogenesis and anti-tumor properties. The material can be used to prepare bone fixation systems or guided bone regeneration membranes.
[0043] The following specific examples illustrate the magnesium-based bone tissue regeneration and repair material coated with Fe3O4@GaP coating, its preparation method and application, and the like. Example 1 High-purity Mg, Mg-13Y, Mg-10Nd, and Mg-20Gd were used as raw materials. The weight ratios of the individual elements in the Mg-4Y-3RE(Nd, Gd) alloy (mass ratio, WE43) were weighed, taking into account the burnout rate. The raw materials were then heated to 700°C in a vacuum melting furnace, melted, and cast into ingots. The ingots were then homogenized in a muffle furnace heated to 400°C for 5 hours and then water-cooled. The ingots were then hot-rolled to produce hot-rolled WE43 plates. The hot-rolled plates were rolled at a temperature of 300°C, with an 80% reduction and a 5% deformation per pass. Each hot-rolling pass was preheated at 300°C for 5 minutes before each hot-rolling pass. The resulting plates were 2 mm thick. The surface oxides were then removed by sandpaper polishing, and the plates were rinsed with deionized water and alcohol and air-dried. The magnesium alloy plate was then immersed in a phosphoric acid solution heated to 50°C under electromagnetic vibration for 20 minutes. The electromagnetic vibration frequency was 100 Hz, the mode was fixed, and the amplitude was 0.5 mm. The phosphating solution was an Fe3O4-doped gallium phosphate solution with a gallium nitrate content of 0.2 mol / L and a phosphoric acid content of 0.4 mol / L. The Fe3O4 particles had a diameter of 80 nm and a mass content of 0.04 mol / L. The pH of the phosphating solution was adjusted to 3.0 using an acid or alkaline solution. After phosphating, the magnesium alloy was removed, rinsed with deionized water and ethanol, and then air-dried to obtain a WE43 alloy bone plate coated with Fe3O4@GaP.
[0044] Performance testing: (1) Micromorphology and composition detection The microstructure and composition of the WE43 alloy bone plate coated with Fe3O4@GaP coating obtained in Example 1 were detected using scanning electron microscopy and EDS. Figure 1 The microscopic morphology shown in FIG. Figure 1 It can be seen that the granular base coating uniformly covers the surface of the WE43 alloy bone plate and has a uniform particle size. Fine particles with a size of approximately 120 nm (point 1) are evenly distributed on the base coating (point 2), and continuous cracks are present on the coating surface. Furthermore, EDS analysis results show that the fine particles (point 1) contain a large amount of Fe and O, with an Fe / O atomic ratio close to 3:4, which is close to the atomic ratio of Fe₃O₄. In contrast, the base coating (point 2) is uniformly distributed with a large amount of Zn, P, and O. Furthermore, scanning electron microscopy measurements show that the thickness of the Fe₃O₄@GaP coating on the WE43 alloy bone plate is 6.9 μm.
[0045] (2) Mechanical properties testing The mechanical properties and corresponding mechanical property attenuation rates of the WE43 alloy bone plates with and without Fe3O4@GaP coatings prepared in Example 1 and after being immersed in Hanks' solution for 3 months were tested and compared, and the results shown in Table 1 below were obtained: As shown in Table 1, the mechanical properties of the WE43 alloy bone plate without the Fe3O4@GaP coating show a tensile strength of 303 MPa, a yield strength of 280 MPa, and an elongation of 19.5%. The WE43 alloy bone plate with the Fe3O4@GaP coating shows a tensile strength of 306 MPa, a yield strength of 289 MPa, and an elongation of 21.3%. After three months of immersion in Hanks' solution, the mechanical properties of the WE43 alloy bone plate without the Fe3O4@GaP coating significantly deteriorate, with a tensile strength of only 143 MPa, a yield strength of 125 MPa, and an elongation of 10.2%. However, the WE43 alloy bone plate with the Fe3O4@GaP coating maintains high mechanical properties after three months of immersion in Hanks' solution, with a tensile strength of 272 MPa, a yield strength of 241 MPa, and an elongation of 18.5%. The Fe3O4@GaP-coated WE43 alloy bone plates met the mechanical performance requirements for biodegradable bone implants both before and after immersion, including yield strength greater than 230 MPa and elongation greater than 15%. Furthermore, after three months of immersion in Hanks' solution, the mechanical properties of the Fe3O4@GaP-coated WE43 alloy bone plates remained at least 80% of those of the unimmersed specimens, demonstrating excellent mechanical stability. This is crucial for the stable application of biodegradable bone fixation systems.
[0046] (3) Corrosion resistance test Polarization test was conducted on the WE43 alloy bone plate with or without Fe3O4@GaP coating prepared in Example 1. Figure 2 The polarization curves shown in FIG2 and the electrochemical performance parameters of the WE43 alloy bone plate with or without Fe3O4@GaP coating in Hanks' solution and its degradation rate after immersion in Hanks' solution for one month are fitted after the polarization test shown in FIG2.
[0047] from Figure 2 The polarization curves and Figure 2It can be seen from the corrosion parameters obtained by fitting the Tafel interval (see Table 2) that the WE43 alloy bone plate coated with Fe3O4@GaP coating obtained by polarization test in Hanks' solution has a more positive corrosion potential and significantly lower corrosion current density, corrosion rate and degradation rate than the WE43 alloy bone plate without Fe3O4@GaP coating, indicating that the Fe3O4@GaP coating can significantly improve the corrosion resistance of magnesium alloy and exhibit good corrosion regulation function.
[0048] (IV) Osteogenesis ability test After three days of culture, the viability of pre-osteoblastic mouse MC-3T3 cells in extracts from uncoated WE43 alloy bone plates at concentrations of 100%, 50%, and 25% Fe3O4@GaP was 37.5%, 74.2%, and 87.5%, respectively. In contrast, the viability of cells in extracts from Fe3O4@GaP-coated WE43 alloy bone plates was 83.8%, 97.2%, and 103.5%, respectively. This indicates that Fe3O4@GaP coating significantly improves the cytocompatibility of WE43 alloy bone plates. The extracts were prepared by placing the WE43 alloy plates in culture medium and immersing them at 37°C for 48 hours to ensure full release of the alloy components. Following immersion, extracts of varying concentrations were prepared according to research needs for subsequent cell experiments or biocompatibility assessments. The same applies below and will not be further detailed. At the same time, the alkaline phosphatase (ALP) level of MC-3T3 cells in the extract of WE43 alloy bone plates coated with Fe3O4@GaP coating was 2.6 times that of the control group (pure titanium standard), indicating that Fe3O4@GaP coating can significantly enhance the differentiation ability of osteoblasts.
[0049] (V) Anti-tumor ability testing The clone morphology of DLM8C3H mouse osteosarcoma cells in the extract of WE43 alloy bone plate with or without Fe3O4@GaP coating was observed, and the corresponding clone numbers were counted. Figure 3 The clone morphology and corresponding clone number statistics of DLM8C3H mouse osteosarcoma cells in the extract of WE43 alloy bone plate with or without Fe3O4@GaP coating are shown, among which, Figure 3 A is the clone morphology of DLM8C3H mouse osteosarcoma cells. Figure 3 B is a statistical diagram of the number of osteosarcoma cell clones in DLM8C3H mice.
[0050] from Figure 3The clonal morphology of DLM8C3H mouse osteosarcoma cells in A shows that the osteosarcoma cell clones in the control group (pure titanium standard) and the WE43 alloy bone plate extract without Fe3O4@GaP coating are densely distributed, with almost no osteosarcoma cell shrinkage and no cell fragments. In contrast, the osteosarcoma cell clones in the WE43 alloy bone plate extract with Fe3O4@GaP coating are sparsely distributed, with irregular edges, and obvious tumor cell shrinkage and increased cell fragments. Figure 3 The statistical results of the number of osteosarcoma cell clones in DLM8C3H mice in Figure B show that compared with the control group (pure titanium standard) and the WE43 alloy bone plate without Fe3O4@GaP coating, the number of osteosarcoma cell clones in the WE43 alloy bone plate coated with Fe3O4@GaP coating was significantly reduced, indicating that the Fe3O4@GaP coating can significantly inhibit the proliferation of tumor cells and even kill tumor cells.
[0051] Example 2 The only difference between it and the above-mentioned embodiment 1 is: In the preparation process of the Fe3O4@GaP-coated WE43 alloy bone plate, a 2mm-thick WE43 alloy sheet was obtained and sanded to remove surface oxides. After rinsing with deionized water and ethanol and drying, the sheet was first subjected to a high-temperature treatment in a hydrogen flame for 4 minutes. During the high-temperature treatment, the sheet was fixed 5 cm above the burner's flame nozzle, and the flame from the burner nozzle burned the sheet surface. After the high-temperature treatment, the sheet was subjected to a reduction treatment in a 700°C H2 atmosphere for 40 minutes. The sheet was then rinsed again with deionized water and ethanol and dried. The sheet was then immersed in a phosphoric acid solution heated to 50°C under electromagnetic vibration for phosphatization for 20 minutes. After phosphatization, the sheet was removed, rinsed with deionized water and ethanol, and dried. Finally, the Fe3O4@GaP-coated WE43 alloy bone plate was obtained.
[0052] Performance testing: (1) Microscopic morphology observation The Fe3O4@GaP coating on the surface of the WE43 alloy plate is in the form of fine particles with a particle size of about 103 nm. There are a small number of discontinuous cracks on the coating surface, and the coating thickness is 8.7 μm.
[0053] (2) Mechanical properties testing The mechanical properties and corresponding mechanical property attenuation rates of the WE43 alloy bone plates with and without the Fe3O4@GaP coating prepared in Example 2 and after being immersed in Hanks' solution for 3 months were tested and compared, and the results shown in Table 3 below were obtained: From the mechanical property test results in Table 3, it can be seen that after the high-temperature calcination and H2 reduction treatment in Example 2, the mechanical properties of the WE43 alloy bone plate coated with Fe3O4@GaP coating are even better, and after being immersed in Hanks' solution for 3 months, the mechanical properties can still be maintained at a high level.
[0054] (3) Corrosion resistance test The corrosion potential, corrosion current density, corrosion rate and degradation rate of the Fe3O4@GaP coated WE43 alloy bone plate obtained by polarization test in Hanks' solution were -1.384 V, 4.1 μA / cm 2 , 53μm / y and 92μm / y.
[0055] (IV) Osteogenesis ability test After culturing MC-3T3 cells for three days in extracts from WE43 alloy bone plates coated with Fe3O4@GaP at concentrations of 100%, 50%, and 25%, the cell viability was 84.6%, 100.3%, and 105.2%, respectively, demonstrating good cytocompatibility. Furthermore, the ALP multiple of MC-3T3 cells in extracts from WE43 alloy bone plates coated with Fe3O4@GaP was 2.9 times higher than that in the control (pure titanium standard), indicating that it promotes osteoblast differentiation.
[0056] (V) Anti-tumor ability testing In addition, the clone number of DLM8C3H mouse osteosarcoma cells in the extract of WE43 alloy bone plates coated with Fe3O4@GaP was only 0.67 times that of the control group (pure titanium standard), indicating that WE43 alloy bone plates coated with Fe3O4@GaP can significantly inhibit the proliferation of tumor cells.
[0057] Example 3 High-purity Mg and Mg-10Li master alloy were used as raw materials. The weight ratios of the elements in the Mg-2Li alloy were weighed, taking into account the burnout rate. The raw materials were then heated to 700°C in a vacuum melting furnace, melted, and cast into ingots. The ingots were then homogenized in a muffle furnace heated to 380°C for 10 hours and then water-cooled. The ingots were then hot-rolled to produce hot-rolled Mg-2Li foils. The hot-rolled foils were rolled at a temperature of 320°C, with a reduction of 95%, a 5% deformation per pass, and a 5-minute preheating period. The resulting foils had a thickness of 0.3 mm. The foils were then sanded to remove surface oxides, rinsed with deionized water and alcohol, and air-dried. The magnesium alloy sheets, screws, and foils were then immersed in a phosphoric acid solution heated to 30°C for 10 minutes under electromagnetic vibration. The frequency of electromagnetic vibration treatment was 100 Hz and the mode was frequency modulation, which was performed reciprocatingly between 20 Hz and 100 Hz. Each frequency treatment lasted 10 seconds and the amplitude was 1 mm. The phosphating solution was Fe3O4-doped gallium phosphate solution with a gallium nitrate content of 0.1 mol / L and a phosphoric acid content of 0.2 mol / L. The Fe3O4 particle size was 80 nm and the mass content was 0.02 mol / L. The pH of the phosphating solution was adjusted to 3.0. After phosphating treatment, the magnesium alloy was removed, rinsed with deionized water and alcohol, and then dried to obtain a Mg-2Li alloy guided bone regeneration membrane coated with Fe3O4@GaP.
[0058] Performance testing: (1) Microscopic morphology observation The Fe3O4@GaP coating on the surface of Mg-2Li alloy is in the form of fine particles with no obvious cracks. The coating thickness is 2.6 μm, indicating that adjusting the process parameters of electromagnetic vibration treatment and phosphating treatment can control the morphology, thickness and crack condition of the coating.
[0059] (2) Mechanical properties testing The Fe3O4@GaP-coated Mg-2Li alloy guided bone regeneration membrane exhibited a tensile strength of 318 MPa, a yield strength of 271 MPa, and an elongation of 28.6%. After three months of immersion in Hanks' solution, the Fe3O4@GaP-coated Mg-2Li alloy guided bone regeneration membrane maintained high mechanical properties and stability, including a tensile strength of 283 MPa, a yield strength of 250 MPa, and an elongation of 20.4%. The mechanical properties, with the exception of elongation, remained over 80% of those of the unimmersed specimen.
[0060] (3) Corrosion resistance test The corrosion potential, corrosion current density, corrosion rate and degradation rate of the Fe3O4@GaP-coated Mg-2Li alloy guided bone regeneration membrane obtained from the polarization test in Hanks' solution were -1.392 V, 4.4 μA / cm 2 , 64μm / y and 97μm / y.
[0061] (IV) Osteogenesis ability test After culturing MC-3T3 cells for three days in extracts from Mg-2Li alloy guided bone regeneration membranes coated with Fe3O4@GaP at concentrations of 100%, 50%, and 25%, the cell viability was 85.7%, 100.5%, and 102.1%, respectively, demonstrating good cytocompatibility. Furthermore, the ALP multiple of MC-3T3 cells in the extracts from the Fe3O4@GaP-coated Mg-2Li alloy guided bone regeneration membrane was 1.9 times higher than that in the control group (pure titanium standard), indicating that it promotes osteoblast differentiation.
[0062] (V) Anti-tumor ability testing In addition, the clone number of DLM8C3H mouse osteosarcoma cells in the extract of Fe3O4@GaP-coated Mg-2Li alloy guided bone regeneration membrane was only 0.80 times that of the control group (pure titanium standard), indicating that the Fe3O4@GaP-coated Mg-2Li alloy guided bone regeneration membrane can also significantly inhibit the proliferation of tumor cells.
[0063] The embodiments of the present application are described above in conjunction with the accompanying drawings. Unless there is a conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the guidance of this application, ordinary technicians in this field can also make many forms without departing from the purpose of this application and the scope of protection of the claims, all of which are within the protection of this application.
Claims
1. A magnesium-based bone tissue regeneration and repair material coated with Fe3O4@GaP coating, characterized in that: That The invention comprises a magnesium-based metal substrate and a Fe3O4@GaP coating layer covered on the surface of the magnesium-based metal substrate.
2. The magnesium-based bone tissue regeneration and repair material coated with Fe3O4@GaP coating according to claim 1, characterized in that: The magnesium-based metal matrix is prepared from pure magnesium or Mg-X alloy, wherein X is selected from one or more of Cu, Zn, Sr, Ca, Ge, Ti, Se, Li, Fe, Sn, Ag, Mn, RE, Ga, Zr, and Al.
3. The magnesium-based bone tissue regeneration and repair material coated with Fe3O4@GaP coating according to claim 2, characterized in that: In the Mg-X alloy, the total mass content of element X is 0.5-20%, and the rest is Mg.
4. The method for preparing a magnesium-based bone tissue regeneration and repair material coated with a Fe3O4@GaP coating according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, preparation of magnesium-based metal matrix: magnesium-based metal material is melted at high temperature and then cast into an ingot, the ingot is placed in a high-temperature furnace at 350-450°C for homogenization treatment for 4-10 hours and then water-cooled, and then the ingot is subjected to hot extrusion or hot rolling deformation treatment to prepare a magnesium-based metal matrix with a specific shape, and then the magnesium-based metal matrix is surface activated and cleaned; S2, preparation of Fe3O4@GaP coating: Under the action of electromagnetic vibration, the magnesium-based metal substrate is immersed in a phosphating solution heated to 30~80℃ for phosphating treatment for 10~30 minutes, then taken out and washed and dried to obtain a magnesium-based bone tissue regeneration and repair material covered with Fe3O4@GaP coating.
5. The method for preparing the magnesium-based bone tissue regeneration and repair material coated with Fe3O4@GaP coating according to claim 4, characterized in that: In step S2: The frequency of the electromagnetic vibration treatment is 10~300Hz, and / or, The electromagnetic vibration treatment mode is frequency modulation or fixed frequency, and / or, The amplitude of the electromagnetic vibration treatment is 0.01~2mm.
6. The method for preparing the magnesium-based bone tissue regeneration and repair material coated with Fe3O4@GaP coating according to claim 4, characterized in that: The phosphating solution contains: 0.01-0.5 mol / L gallium nitrate, 0.02-1 mol / L phosphoric acid, 0.005-0.5 mol / L Fe3O4, wherein the particle size of the Fe3O4 is 50-500 nm, and the pH of the phosphating solution is adjusted to 2.5-4.0 with acid or alkali solution.
7. The method for preparing the magnesium-based bone tissue regeneration and repair material coated with Fe3O4@GaP coating according to claim 4, characterized in that: In the step S1, The ingot is subjected to hot extrusion deformation to prepare a hot extruded magnesium alloy rod, wherein the hot extrusion extrusion ratio is 1:9-36 and the extrusion temperature is 250-450°C; or, The ingot is hot rolled to produce hot-rolled plates or foils, wherein the rolling temperature of the hot-rolled plates and foils is 250-480°C, the deformation amount of each pass is 2-10%, and preheating for 5-10 minutes is performed before each hot rolling pass.
8. The method for preparing the magnesium-based bone tissue regeneration and repair material coated with Fe3O4@GaP coating according to claim 4, characterized in that: In step S1, the process of performing surface activation and cleaning treatment on the magnesium-based metal substrate includes: (I) Use sandpaper to remove surface oxides, (II) Rinse with deionized water and alcohol and let dry.
9. The method for preparing the magnesium-based bone tissue regeneration and repair material coated with Fe3O4@GaP coating according to claim 4, characterized in that: In step S1, the process of performing surface activation and cleaning treatment on the magnesium-based metal substrate includes: (I) Use sandpaper to remove surface oxides; (II) Rinse with deionized water and alcohol and then dry; (III) placing the magnesium-based metal substrate in a hydrogen flame for high temperature treatment for 3 to 5 minutes; (IV) placing the magnesium-based metal substrate in a reducing atmosphere at 600-800°C for 30-60 minutes; (V) Rinse again with deionized water and alcohol and allow to dry.
10. Use of the magnesium-based bone tissue regeneration and repair material coated with the Fe3O4@GaP coating according to any one of claims 1 to 3 in the preparation of a bone fixation system or a guided bone regeneration membrane.